A REVISIT OF ASSISTED REPRODUCTION TECHNOLOGY AND THE HUMANIZATION PARADIGM - Suleiman Zubair; Abubakar Sadik Mustafa; Ahmad Ali Badri; Ali Reza Lari2; Mohammadreza Daroonparvar; Fauzi Hussin (PERINTIS eJournal, 2021)
Assisted Reproductive Technology (ART) has been debated over a period of time between its permissibility and otherwise. While it has been widely accepted in classical terms, religion generally seeks to regulate its varied application according to their various guiding principles. The fact that ART intrudes the domains of human life that undermines human dignity has made countries to establish regulatory laws. However, these laws have been agreed to be rather negligent and not encompassing to protect the human dignity although the question of the limits and definition of dignity is another area of debate as the article mentions. The effects of ART and how present practice undermines human dignity are objectively highlighted. Various religious views are summarized and a case is made for Islam as being the most comprehensive way that looks at the issue from various relevant perspectives and further advocate that bioethics is guided by Islamic rules.